Combining Project Based Learning and Cooperative Learning Strategies in a Geotechnical Engineering Course - Torrijo, Francisco Javier; Garzón-Roca, Julio; Cobos, Guillermo; Eguibar, Miguel Ángel (Education sciences, 2021)
This paper presents the implementation of a learning methodology following a student-centred approach. The methodology is based on the use of project based and cooperative learning and mainly consists of commissioning students to prepare a presentation on a topic of their subject. Students work in groups, and later must deliver a real lecture to their colleagues. The proposed methodology was applied across 7 years and its implementation was monitored via day-to-day observations, annual surveys, the gathering of direct feedback as well as by analysing the students’ academic performance. Results show the ability of the proposed learning methodology to enhance motivation and engagement of students, facilitate the improvement of four soft skills (team-working, practical thinking, effective communication and critical thinking), eliminate absenteeism and facilitate long-term retention of the knowledge and skills acquired in a subject.